Characterisation of penicillinase producing gonococci isolated in Munich, 1981-6. Issue 1 (February 1988) - Abeck, D; Johnson, A P; Korting, H C
Abstract : Twenty three penicillinase producing strains of Neisseria gonorrhoeae (PPNG) isolated in Munich from 1981 to 1986 were characterised in terms of their plasmid content, auxotypes, protein I serovars, and sensitivity to antibiotics. Sixteen strains (70%) harboured a 4.4 megadalton plasmid, with 13 of these strains also containing a 24.4 megadalton plasmid. Seven strains (30%) contained a 3.2 megadalton plasmid, with only one of them containing a 24.4 megadalton plasmid. Thirteen strains (57%) were prototrophic, eight (35%) required proline, one required arginine, and one required proline and arginine for growth. Serovar analysis showed that 16 strains (70%) belonged to the protein IB serogroup and comprised four serovars (IB-1, IB-5, IB-7, and IB-8). The seven strains belonging to the IA serogroup also comprised four serovars (IA-2, IA-4, IA-6, and IA-10). Although 18 different categories of plasmid, auxotype, and serovar were found in the 23 PPNG strains, there was a similarity between the auxotypes in terms of the range of serovars they comprised. Measurement of minimum inhibitory concentrations (MICs) of antibiotics for the strains showed that they were all susceptible in vitro to spectinomycin (MIC less than or equal to 32 mg/l), enoxacin (MIC less than or equal to 0.25 mg/l), cefotaxime, ciprofloxacin, and ceftriaxone (MICs less than or equal to 0.064 mg/l), whereas about half showed some resistance to tetracycline or cefotiam, or both.